Interface engineering for highly-reliable 65 nm-node Cu/ULK (k=2.6) interconnect integration - Ishii, A.; Matsumoto, S.; Hattori, T.; Suzuki, S.; Isono, S.; Iwasaki, A.; Tomita, K.; Hashimoto, K.; Tawa, S.; Furusawa, T.; Kodama, D.; Ogawa, S.; et al. (Proceedings of the IEEE 2005 International Interconnect Technology Conference, 2005, 2005)
Interface engineering technologies are developed for highly-reliable 65 nm-node Cu/low-k interconnect integration using a ULK dielectric (k=2.6) in a hybrid ILD structure. For electromigration (EM) reliability, the mechanical integrity at the SiOC/SiC(N,O) interface exposed on the via sidewalls is found to be critical. For TDDB reliability, reduction in Cu-containing defects at the SiC(N,O)/SiOC interface at the top of the metal line is critical. By optimizing these interfaces, the EM and the TDDB lifetimes are significantly improved.